Brachylaena elliptica and B. ilicifolia (Asteraceae): A Comparative Analysis of their Ethnomedicinal Uses, Phytochemistry and Biological Activities - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2020)
Brachylaena elliptica and B. ilicifolia are shrubs or small trees widely used as traditional medicines in southern Africa. There is need to evaluate the existence of any correlation between the medicinal uses, phytochemistry and pharmacological properties of the two species. Therefore, in this review, analyses of the ethnomedicinal uses, phytochemistry and biological activities of B. elliptica and B. ilicifolia are presented. Results of the current study are based on data derived from several online databases such as Scopus, Google Scholar, PubMed and Science Direct, and pre-electronic sources such as scientific publications, books, dissertations, book chapters and journal articles. The articles published between 1941 and 2020 were used in this study. The leaves and roots of B. elliptica and B. ilicifolia are mainly used as a mouthwash and ethnoveterinary medicines, and traditional medicines for backache, hysteria, ulcers of the mouth, diabetes, gastro-intestinal and respiratory problems. This study showed that sesquiterpene lactones, alkaloids, essential oils, flavonoids, flavonols, phenols, proanthocyanidins, saponins and tannins have been identified from aerial parts and leaves of B. elliptica and B. ilicifolia. The leaf extracts and compounds isolated from the species exhibited antibacterial, antidiabetic, antioxidant and cytotoxicity activities. There is a need for extensive phytochemical, pharmacological and toxicological studies of crude extracts and compounds isolated from B. elliptica and B. ilicifolia.